Maus-tratos contra crianças e adolescentes: limites e possibilidades de atuação de profissionais de saúde - VELOSO, Milene Maria Xavier (Universidade Federal do Pará, 2020)
The issue of maltreatment of children and adolescents constitutes a serious public health problem, since it can produce morbidity and / or mortality, but trouble for your development throughout the life cycle. In this sense health professionals have an important role in identification, reporting and handling of cases. This study aimed to investigate the knowledge of health professionals about maltreatment of children and adolescents, their attitudes and difficulties for the management of this phenomenon and to analyze the profile of notifications of violence carried out in the city of Belém-PA to propose possibilities performance. The study was developed from two axes: secondary data collected in Notification of diseases Notification System (SINAN-Net), the city of Belém-PA, in the 2009-2013 period, and primary data from the application two structured questionnaires in 174 health professionals from primary care of an administrative district of the same township. Data were analyzed from BioEstat 5.3. program. We identified 6,381 cases of violence against children reported in the period. The most prevalent type of violence was sexual, associated with physical and / or psychological violence, with an annual average of 89.55% for girls, with higher prevalence in the age group 11-14 years (39.97%). For boys sexual violence was also the most prevalent type (74.48%), followed by physical violence, but more often in the age group 6-10 years (42.46%). The violence was mainly practiced by individuals identified as friends or acquaintances, followed by stepfather. The study, conducted with health professionals, showed that about 30% reported never having seen a child or teenager and victim of some type of violence in their routine work, especially for community health agents. Negligence was perceived by 60.74% of the professionals, but only 19.05% of those reported have it notified. Moreover, sexual abuse was less above (24.14%), but exhibited higher reporting rate (50.0%). Physical violence was reported by only 39.47% of the professionals identified and psychological violence, by 34.88%. Among the top-level technicians 50.0% said they did not know the notification form and 86.11% never used. In addition, 25.82% reported having experienced some form of violence in childhood and / or adolescence. The data demonstrate the urgency of public policies aimed at families and the community to the cycles of violence against children and adolescents are stopped and other community living opportunities can be encouraged. Allied to this, a permanent education policy geared to health professionals is essential, so that the regulations can be effected in the daily practice of these professionals, ensuring full protection to children and adolescents from intra and inter-sectoral actions.